A Comparative Study of Success Factors among Communities in the Coal Mining and Oil Palm Plantation Sectors in Satui District - Gilbert Patterson Owen (Geosfera: Jurnal Penelitian Geografi, 2025)
This study examines the socio-economic characteristics of labor in the coal mining and oil palm plantation sectors in Satui District, Indonesia, focusing on education level, working hours, and income. A quantitative descriptive approach was applied, with data collected from 100 respondents equally representing both sectors. Cross-tabulation and Chi-square tests were used to analyze differences in labor characteristics and their impact on income and household welfare.Findings reveal that workers in the coal mining sector generally have higher education, longer and more structured working hours, and more stable monthly income, while workers in the oil palm plantation sector are dominated by lower-educated labor with flexible working hours and variable income. Education significantly influences job position and income stability, especially in mining, and longer working hours correlate positively with income in both sectors.The study highlights that sectoral differences in education and working patterns strongly affect labor income and household economic conditions. These results provide empirical evidence to support labor policy formulation and regional economic development strategies tailored to the characteristics of each sector.